Multimedia Thesaurus: A Case of Designing and Prospects for Using in Engineering Education - M. M. Bazhutina (Высшее образование в России)
The paper deals with the technology for the creation and use of an individual multimedia bilingual thesaurus as a tool for the integration of the foreign language and engineering disciplines at a technical university. The stages of designing and testing an individual thesaurus in vocational English language classes with students, majoring in automobile engineering, are described. Building on the achievements in thesaurus modelling in integrative foreign languages and professional disciplines teaching, the author presents her own technology for creating an individual English-Russian multimedia thesaurus, devoted to the automobile design, and the sequence of formation of speech skills in foreign language communication of engineers on its basis. The process of creating such thesaurus takes place at two levels of integration: intra-subject (interrelationship of all types of speech activity) and interdisciplinary (didactic synthesis of language and engineering disciplines). At the same time, the author outlines the areas of the near and further integration of the discipline «Professional English» and engineering disciplines, which is aimed at developing interdisciplinary thinking of engineering students. The author emphasizes the fact that successful teaching cross-cultural engineering communication requires outlining the content of learning situations, the modelling of which is the English language instructor’s responsibility. In order to organize this work, students are supposed to create a contextual part of the thesaurus from which the instructor singles out speech patterns. The selected speech patterns are mastered in a series of exercises and tasks prior to learning situations. The conclusion outlines ways of the further interdisciplinary integration by means of thesaurus modelling of professional subject areas.